TEACHER OF THE XXI CENTURY: WHAT IS HE? - Nodira Kushakova (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2021)
This article reveals the ability to effectively carry out educational work in the learning process, to form a high morality, a sense of patriotism, hard work, and independence in a schoolchild is another element of pedagogical skill.